Nutrient Deficiencies Are Common Prior to Bariatric Surgery. (21st June 2017) - Frame‐Peterson, Leigh A.; Megill, Robin D.; Carobrese, Suzanne; Schweitzer, Michael
Abstract : Obesity, defined as a body mass index >30 kg/m 2, is a growing worldwide epidemic currently effecting 1 in 10 adults, with rates as high as 40% in the United States. The only proven long‐term treatment of severe obesity on a population level is surgical modification of the gastrointestinal anatomy to induce weight loss, termed bariatric surgery . With adequate physician guidance and appropriate candidate criteria, bariatric surgery is an option for effective long‐term treatment of obesity and its related comorbidities. Complications of bariatric surgery can be seen in patients who are not compliant to the recommended lifestyle and dietary changes required following bariatric surgery, including nausea, vomiting, dumping syndrome, acid reflux, and nutrition deficiencies. Despite caloric density, the diet of patients prior to bariatric surgery is often of poor nutrition quality and does not meet recommended dietary guidelines for micronutrient intake, making this an at‐risk population for micronutrient malnutrition. Currently, improvements are needed in standardization of nutrition assessment as well as micronutrient cutoffs for deficiency and insufficiency. In the meantime, utilizing our current tools to conduct nutrition assessment at baseline and implement supplementation where necessary may improve the nutrition status of patients undergoing bariatric surgery, both before and after surgery, which may improve their surgical outcomes.